Gestão comportamental: ferramentas que contribuem para o comportamento seguro - Silveira, Fernanda Soares (Universidade do Vale do Rio dos Sinos, 2015)
It is known that an effective safety management can be obtained through the development of physical conditions in the workplace, safety management practices and safe behavior. For Geller (1994 apud BLEY, 2006), the safety culture in organizations must consider three very important factors, which are: physical conditions (equipment, tools), personal factors (attitudes and personality) and behavioral factors (actions aimed safety or risk exposure within the organization). Although the legislation has a number of standards that deal with physical conditions and management procedures, an issue to be worked by companies is how to develop a preventive culture with all its employees, regardless of hierarchical level. This article aims to facilitate the understanding of the use of tools and behavioral practices, and how they can contribute to the safety culture, inside and outside of organizations. This paper discusses the tools Behavioral Management used in a company in the metallurgical industry.
Keywords: Comportamento; Acidentes; Prevenção; Cultura; Segurança; Behavior; Accidents; Prevention; Culture; Safety